Dorsal Medullary Infarction: Distinct Syndrome of Isolated Central Vestibulopathy. Issue 11 (November 2015) - Lee, Sun-Uk; Park, Seong-Ho; Park, Jeong-Jin; Kim, Hyo Jung; Han, Moon-Ku; Bae, Hee-Joon; Kim, Ji-Soo
Abstract : Background and Purpose—: The characteristics of infarctions restricted to the dorsal medulla have received little attention. This study aimed to define the distinct clinical features of dorsal medullary infarction. Methods—: Of the 172 patients with a diagnosis of medullary infarction at Seoul National University Bundang Hospital from 2003 to 2014, 18 patients with isolated dorsal medullary infarction were subjected to analyses of clinical and laboratory findings. Results—: All patients presented acute isolated vestibular syndrome with dizziness/vertigo and imbalance. Almost all patients (17/18, 94%) showed the signs from involvements of the vestibular nuclei, nucleus prepositus hypoglossi, or inferior cerebellar peduncle, which included direction-changing gaze-evoked nystagmus (n=12), negative head-impulse tests (n=8), skew deviation (n=7), central patterns of head-shaking nystagmus (n=6), and spontaneous nystagmus (n=2). Initial magnetic resonance imagings including diffusion-weighted images were negative in 7 patients (39%). Twelve patients (67%) showed a progression and developed additional neurological abnormalities, but the neurological outcomes were favorable. Conclusions—: The presence of central vestibular signs allows bedside differentiation of isolated vestibular syndrome because of dorsal medullary infarction from acute peripheral vestibular disorders. Because initially false-negative magnetic resonance imagings and subsequent progression are frequent in dorsal medullary infarction, early recognition through scrutinized evaluation is important for proper managements.